Efektifitas Variasi Plat 4//4 dan 5//5 Elektroda Al/Cu terhadap Kinerja Generator Penghasil Gas Hidrogen - Deandra Savira; Rahadian Zainul (Dinasti Research, 2021)
This study aims to compare the effectiveness of plate variations 4//4 and 5//5 Al/Cu on the performance of hydrogen gas generators. The method used is electrolysis using electrolytes H2O and CH3COONa. The result obtained is that the 4/4 Al/Cu electrode plate variation is more effective in producing hydrogen gas during electrolysis than the 5/5 al/cu electrode plate variation. The 4/4 plate variation produces hydrogen gas with 8 ml and 102 ml of H2O and CH3COONa electrolytes, respectively. The use of electrolytes in the form of salt and variations of the electrode plates during the electrolysis process affect the yield of hydrogen gas produced using a hydrogen generator.